Understanding Property Market Dynamics: Insights from Modelling the Supply-Side Adjustment Mechanism - Nanthakumaran, Nanda; Watkins, Craig; Orr, Allison (Environment and planning. A, 2000)
The volatility of commercial property markets in the United Kingdom has stimulated the development of explanatory models of ‘price’ determination. These models have tended to focus on the demand-side as the driver of change. A corollary of this is that, despite the fact that construction lags are known to exacerbate cyclical fluctuations, the supply-side adjustment mechanism has been subject to relatively little research effort. In this paper the authors develop a new model of commercial property markets in the United Kingdom. The model is adapted from Poterba's two-equation asset-market approach to modelling the housing market. The first equation is an arbitrage relationship where the return on property is made up of rent, as determined in the user market for property services, and the capital gain, which is dependent on the return on alternative assets. This can be interpreted as a ‘stock’ demand equation. The second equation explains that ‘flow’ supply is determined by real capital values. The long-run empirical generalisation of the two-equation model allows the authors to estimate two key behavioural parameters required in explaining supply-side adjustment to market change. First, the authors interpret the coefficient on the capital value variable in the supply equation as an estimate of the long-run ‘price’ elasticity of supply. Second, from the demand equation, they estimate the extent to which new supply can act as an ‘automatic stabiliser’ on property values. It is argued that although increases in demand drive up property values, new development is also initiated and will, in turn, dampen down the growth in real capital values. The equations are estimated for the office, industrial, and retail sectors. Although there are no comparable estimates of supply elasticities in the real estate economics literature, the results are generally consistent with prior knowledge. Estimates of the stabiliser effect are also plausible and, taken together, the supply-side parameters help provide insights required in understanding property market dynamics in the last twenty-five years.